2019
DOI: 10.1371/journal.pone.0226165
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin enhances sensitization to the egg-white allergen ovalbumin in rats

Abstract: Enhancement of oral absorption of food allergens by non-steroidal anti-inflammatory drugs (NSAIDs), especially aspirin, is considered an exacerbating factor in the development of food allergies. In this study, we examined the effect of aspirin on oral sensitization to and absorption of the egg-white allergen ovalbumin (OVA) in rats. The absorption of OVA was evaluated by measuring the plasma concentration of OVA after oral administration by gavage. To evaluate oral sensitization to OVA, plasma levels of immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The results indicated that canna starch intake inhibited the accumulation of OVA in the liver of food allergy model mice. Although it has been reported that increased allergen absorption exacerbates symptoms in rats [27], in the current study, a decrease in allergen uptake by canna starch ingestion in the food allergy model mice may be one reason for the suppression of anaphylactic symptoms.…”
Section: Discussionmentioning
confidence: 54%
“…The results indicated that canna starch intake inhibited the accumulation of OVA in the liver of food allergy model mice. Although it has been reported that increased allergen absorption exacerbates symptoms in rats [27], in the current study, a decrease in allergen uptake by canna starch ingestion in the food allergy model mice may be one reason for the suppression of anaphylactic symptoms.…”
Section: Discussionmentioning
confidence: 54%
“…To evaluate the sensitization to gluten and its components, plasma levels of IgE and IgG 1 Abs specific for gluten, gliadin, glutenin, and ω5-gliadin were determined by an ELISA in accordance with our previous report [ 26 ] with a modification. To determine the levels of gluten and its component-specific IgE Abs in plasma, each well of an ELISA plate was coated with 1 µg/mL MARE-1 dissolved in PBS (100 µL, pH 7.4) overnight at 4 °C.…”
Section: Methodsmentioning
confidence: 99%